Community engagement and the social context of targeted malaria treatment: a qualitative study in Kayin (Karen) State, Myanmar. (December 2017) - Sahan, Kate; Pell, Christopher; Smithuis, Frank; Phyo, Aung; Maung, Sai; Indrasuta, Chanida; Dondorp, Arjen; White, Nicholas; Day, Nicholas; Seidlein, Lorenz; Cheah, Phaik
Abstract Background The spread of artemisinin-resistance inPlasmodium falciparum is a threat to current global malaria control initiatives. Targeted malaria treatment (TMT), which combines mass anti-malarial administration with conventional malaria prevention and control measures, has been proposed as a strategy to tackle this problem. The effectiveness of TMT depends on high levels of population coverage and is influenced by accompanying community engagement activities and the local social context. The article explores how these factors influenced attitudes and behaviours towards TMT in Kayin (Karen) State, Myanmar. Methods Semi-structured interviews were conducted with villagers from study villages (N = 31) and TMT project staff (N = 14) between March and July 2015. Results Community engagement consisted of a range of activities to communicate the local malaria situation (including anti-malarial drug resistance and asymptomatic malaria), the aims of the TMT project, and its potential benefits. Community engagement was seen by staff as integral to the TMT project as a whole and not a sub-set of activities. Attitudes towards TMT (including towards community engagement) showed that developing trusting relationships helped foster participation. After initial wariness, staff received hospitality and acceptance among villagers. Offering healthcare alongside TMT proved mutually beneficial for the study and villagers. A handful of more socially-mobile and wealthy community members were reluctant to participate. The challenges of community engagement included time constraints and the isolation of the community with its limited infrastructure and a history of conflict. Conclusions Community engagement had to be responsive to the local community even though staff faced time constraints. Understanding the social context of engagement helped TMT to foster respectful and trusting relationships. The complex relationship between the local context and community engagement complicated evaluation of the community strategy. Nonetheless, the project did record high levels of population coverage.